13s-3=10

Simple and best practice solution for 13s-3=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13s-3=10 equation:


Simplifying
13s + -3 = 10

Reorder the terms:
-3 + 13s = 10

Solving
-3 + 13s = 10

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 13s = 10 + 3

Combine like terms: -3 + 3 = 0
0 + 13s = 10 + 3
13s = 10 + 3

Combine like terms: 10 + 3 = 13
13s = 13

Divide each side by '13'.
s = 1

Simplifying
s = 1

See similar equations:

| x+54+x+82+56=180 | | -4(n+7)+1=-4n-23 | | 150=4(6*5)+2(6h) | | bx+a=ab | | 7x+14=3x+34 | | 2x-7=-6X+17 | | 4(4S+2)=136 | | (6+y)-Y=6 | | .5x+1=-.67+15 | | 6x^2+24x=42 | | 3y-3-5y=3-2y | | 4n-5=6 | | -7m-4m=22 | | 150=4(6*4)+2(6h) | | l+8=26 | | f*-2=2*-2+5 | | sin(x)=1.22 | | w-8=106 | | 5x+3=5x-10+77 | | -3(5+7x)=-40+4x | | 12+6m=7m-6(m-2) | | r+4=15 | | 0=2.4x^2+4.2x+1.2 | | 18.75+x=26.55 | | 4x-8=5x+5+75 | | 6x-2x+60= | | 2(3d-4)=2(2d+6) | | y=-3+2+5 | | (3v+5)(8+v)=0 | | 3r-18=3 | | K^2+7x=0 | | -13/5+21/2x=-29/40 |

Equations solver categories